HUBUNGAN PEKERJAAN TERHADAP KEJADIAN HERNIA INGUINALIS DI RUMAH SAKIT PETAMINA BINTANG AMIN HUSADA PERIODE OKTOBER 2021 – MARET 2022 - Aditya Ramadhani; Festy Ladyani Mustofa; Eko Purnanto; Tessa Syahriani (Jurnal Medika Malahayati, 2022)
Hernia is a protrusion of the contents of a cavity, the weakest part of the musculoaponeurotic part of the abdominal, the hernia consists of a ring bag and the contents of the hernia. All cases of hernia occur through a weak fissure or potential weakness in the abdominal. due to repeated or sustained increases in intra-abdominal pressure. An inguinal hernia is a medical condition characterized by the protrusion of soft tissue, through the weak part of the lower abdominal in the groin. To find out the work correlation with Inguinal Hernia patients at Pertamina Bintang Amin Hospital October 2021 - March 2022. This type of research is observational analytic with secondary data using medical record data. The subject of this research is the patient in the medical record of Pertamina Bintang Amin Husada Hospital October 2021 - March 2022. Data analysis using Chi Square Correlation Test. Based on the results of the research conducted, the P value obtained is 0.031, that Ha is less than 0.05 which is a work correlation to the incidence of inguinal hernia at Pertamina Bintang Amin Husada Hospital October 2021 - March 2022. There was a correlation between heavy work and Inguinal Hernia patients at Pertamina Bintang Amin Hospital October 2021 – March 2022.